Triplet-based architecture and its process migration mechanism - Bin Liu; Zhi-Chen Tong; Yu-Jin Gao (2009 International Conference on Machine Learning and Cybernetics, 2009)
This paper introduced scalable triplet-based computer architecture (TriBA) that is designed according to the decomposition method of complex problems. The specialized process migration mechanism for TriBA (PMMFT), which includes register tables to help record the process and related migration information, is proposed. By retransferring the messages related to the migrated process during migration, PMMFT decreases the process residual dependency and improves the process communication transparency. By the checkpoint-based process migration strategy, PMMFT can avoid the migration failure due to the possible node failure related to the migration process. In experiment, PMMFT is adopted by THINDLBA, a dynamic load balancing algorithm specially designed for TriBA, the results verified the availability of PMMFT.